UNDERSTANDING THE CONCEPT OF COPYRIGHT IN CIVIL LAW AND ISLAM - Shilvia, Cut Vera; Sabrina, Azkiya S; shabarullah, shabarullah (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2022)
Copyright is one of the rights that has been given legal protection in Indonesia as a result of extraordinary creativity, works that are used by both the individual concerned and the general public. The purpose of this study is to gain an understanding of copyright infringement in both Islamic and civil law. This desk research aims to answer questions about Islamic and civil law perspectives on copyright. In addition, this research discusses how civil law and Islamic principles protect copyright. The study shows that copyright in Islamic law is called haq al-ibtikar - the right to the first creation. Only that which is in accordance with the values and norms of the Islamic religion is accepted and protected. If the work contradicts Islamic principles, it is not recognised as a copyrightable work and no protection is given to the work.